Relationship of strength, joint kinesthesia, and plantar tactile sensation to dynamic and static postural stability among patients with anterior cruciate ligament reconstruction - Hu, Shanshan; Ma, Xiaoli; Ma, Xiaoyuan; Sun, Wei; Zhou, Zhipeng; Chen, Yan; Song, Qipeng (Frontiers in Physiology, 2023)
Objective: Postural stability is essential for high-level physical activities after anterior cruciate ligament reconstruction (ACLR). This study was conducted to investigate the relationship of muscle strength, joint kinesthesia, and plantar tactile sensation to dynamic and static postural stability among patients with ACLR. Methods: Forty-four patients over six months post ACLR (age: 27.9±6.8 years, height: 181.7±8.7 cm, weight: 80.6±9.4 kg, postoperative duration: 10.3±3.6 months) participated in this study. Their static and dynamic postural stability, muscle strength, hamstring/quadriceps ratio, joint kinesthesia, and plantar tactile sensation were measured. Partial correlations were used to determine the correlation of the above-mentioned variables with time to stabilization (TTS) and root mean square of the center of pressure (COP-RMS) in anterior-posterior (AP) and mediolateral (ML) directions. Results: Both TTSAP and TTSML were related to muscle strength and joint kinesthesia of knee flexion and extension; COP-RMSAP was correlated with plantar tactile sensations at great toe and arch, while COP-RMSML was correlated with joint kinesthesia of knee flexion, and plantar tactile sensation at great toe and heel. Dynamic stability was sequentially correlated with strength and joint kinesthesia, while static stability was sequentially correlated with plantar tactile sensation and joint kinesthesia. Conclusion: Among patients with ACLR, strength is related to dynamic postural stability, joint kinesthesia is related to dynamic and static postural stability, and plantar tactile sensation is related to static postural stability. Strength has a higher level of relationship to dynamic stability than joint kinesthesia, and plantar tactile sensation has a higher level of relationship to static stability than joint kinesthesia.